Nauczyciel od czytania… czyli kto? .......... 13 - Kawoń-Noga, Dagmara (Skąd się biorą czytelnicy?, 2025)
TEACHERS OF READING: WHAT ARE THEY EXACTLY?The article attempts to find optimal teaching methods to promote reading among children and teenagers. Starting with the concepts of neurodidactics, the impact of reading on the human brain, and the benefits of reading, the author indicates the tasks school has regarding reader education and literary awareness (based on the teaching curricula) and compares them with the results of national studies of readership. She analyzes the teacher’s role as a potential ambassador of reading who can effectively influence the behaviors and habits of students of every age. The conclusion is not so much the need to modify the teaching methods as the attitudes of the educators themselves. The author presents three approaches that she deems relevant to the process of teaching to read and to promoting the habit of reading and she illustrates them with three film heroes: John Keating (Dead Poets Society, directed by Peter Weir), LouAnne Johnson (Dangerous Minds, directed by John N. Smith), and Bernardo Villalobos (CODA, directed by Sian Heder).